2021
DOI: 10.1111/sdi.12979
|View full text |Cite
|
Sign up to set email alerts
|

Pain on arteriovenous fistula cannulation: A narrative review

Abstract: In the present narrative review, we performed a thorough research of all the available studies on AVF puncture pain management.Electronic databases including Medline, Embase, Scopus, and Web of Science were searched from 1950 until the end of June 2020. The key words used were "pain," "arteriovenous fistula," and "hemodialysis." We also searched the references on the full texts of the studies

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 52 publications
1
9
2
Order By: Relevance
“…These findings suggest that pain associated with vascular access cannulation is a common concern for patients undergoing haemodialysis. However, the severity of pain reported can vary across studies [ 6 , 11 , 13 , 14 , 15 ]. In the present study, the mean pain level reported by the participants was consistent with the mild-to-moderate pain reported in previous research [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings suggest that pain associated with vascular access cannulation is a common concern for patients undergoing haemodialysis. However, the severity of pain reported can vary across studies [ 6 , 11 , 13 , 14 , 15 ]. In the present study, the mean pain level reported by the participants was consistent with the mild-to-moderate pain reported in previous research [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The main cannulation techniques are rope-ladder, buttonhole, and puncture [ 4 , 5 ]. It is estimated that an average haemodialysis patient undergoes 312 cannulations per year [ 6 ]. This procedure harms the patient and provokes anxiety due to fear, pain, and distress [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, this study also evaluated the analgesic effect of music when used in conjunction with other analgesics. Topical analgesics are widely used during hemodialysis to relieve cannulation pain (26). The previously mentioned study had issues with external validity because patients using analgesics were excluded from analysis (Supplemental a The prescription dry body weight for dialysis is the weight at which the patient's volume status is neither overhydrated nor underhydrated.…”
Section: Discussionmentioning
confidence: 99%
“…Patients receiving dialysis have severely decreased quality of life, 28 and pain is reported as one of the essential outcomes for the majority of patients with chronic kidney disease. 29 , 30 Several studies have found that patients cannulated with the buttonhole technique experience less pain compared with the rope-ladder technique. 31 However, not all studies have confirmed this.…”
Section: Discussionmentioning
confidence: 99%